2009
DOI: 10.1542/peds.2008-1302
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized Nasal Intermittent Positive-Pressure Ventilation and Neonatal Outcomes

Abstract: Background-Current literature suggests that use of synchronized nasal intermittent positive pressure ventilation (SNIPPV), following extubation, reduces the rate of reintubation compared to nasal continuous positive airway pressure (NCPAP). However, there is limited information available on the outcomes of infants managed with SNIPPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 49 publications
2
51
1
7
Order By: Relevance
“…Furthermore, ventilator-associated pneumonia may contribute to the ongoing inflammation in the lung, eventually leading to BPD. Three studies 21,24,25 suggest that early extubation to NIPPV may be an important modifier of BPD, even if the total duration of mechanical ventilation is not different. In a large retrospective study, Bhandari et al 24 reported that use of sNIPPV was associated with decreased BPD, BPD/death, neurodevelopmental impairment and neurodevelopmental impairment/death when compared with infants managed on NCPAP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ventilator-associated pneumonia may contribute to the ongoing inflammation in the lung, eventually leading to BPD. Three studies 21,24,25 suggest that early extubation to NIPPV may be an important modifier of BPD, even if the total duration of mechanical ventilation is not different. In a large retrospective study, Bhandari et al 24 reported that use of sNIPPV was associated with decreased BPD, BPD/death, neurodevelopmental impairment and neurodevelopmental impairment/death when compared with infants managed on NCPAP.…”
Section: Discussionmentioning
confidence: 99%
“…13 Clinical retrospective data from the NICHD/NRN benchmarking trial was used to evaluate the use of SNIPPV in infants p1250 g birth weight. 27 The use of SNIPPV in three birth weight sub-groups (500-750, 751-1000, 1001-1250 g, decided a priori) was . 27 Selected studies of SNIPPV and NIPPV use in neonates have been summarized in Tables 1 and 2, respectively.…”
Section: (S)nippv Complicationsmentioning
confidence: 99%
“…27 The use of SNIPPV in three birth weight sub-groups (500-750, 751-1000, 1001-1250 g, decided a priori) was . 27 Selected studies of SNIPPV and NIPPV use in neonates have been summarized in Tables 1 and 2, respectively.…”
Section: (S)nippv Complicationsmentioning
confidence: 99%
“…Nonsynchronized nasal ventilation may be better than even short periods of invasive SIMV, in terms of decreasing ventilator-associated lung injury. Recently, in a large retrospective study, 38 SNIPPV when compared to NCPAP in preterm neonates with birth weight of 500 to 750 g, is associated with significantly less BPD, BPD/death, neurodevelopmental impairment or neurodevelopmental impairment/death.…”
Section: Ncpap Versus Nippvmentioning
confidence: 99%